Dialogical Democracy and the Problem of Deep Politics - Tutui Viorel (Argumentum: Journal of the Seminar of Discursive Logic, Argumentation Theory and Rhetoric, 2011)
Abstract : A fundamental challenge of contemporary political philosophy is how to solve the problem of the legitimacy of political decisions in the context of the deep comprehensive (moral, philosophical, religious, and so on) disagreements that affect pluralist democratic societies. How can citizens of a democracy agree on political decisions without abandoning their most fundamental commitments and without excluding those who wish to remain loyal to their principles? This is the problem of deep politics. In this paper I will analyze the theory of dialogical democracy developed by Robert B. Talisse. This theory is based on his view regarding the principles of folk epistemology to which all of us are already implicitly committed and which entail the acceptance of a democratic political and social framework. I will argue that his attempt to offer an epistemic justification to deliberative democracy is vulnerable to the same kind of objections he raises against the alternative deliberative models of democracy and that an aggregative conception is preferable.